Percentage of Boar Sperm Motility in BTS Dilution (Beltsville Thawing Solution) at Baturiti Artificial Insemination Center - I P. S., Ranggadana; Sumardani, N. L. G.; Mariani, N. P. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to determine the parameters of fresh sperm quality of boarat Baturiti Artificial Insemination Center. Data collected in study consists of primary data and secondary data. Primary data is obtained by survey techniques, interviews and direct observations, while secondary data is obtained through records of the results of boar semen storage during the month of October 2018 at UPT Baturiti Artificial Insemination Center. The variables observed in study covers volume of sperm, motility, and total boar semen production. Study results show that the average percentage of boar semen at UPT Baturiti Artificial Insemination Center in October 2018 consisted of the volume of semen which was 207 ml, the percentage of individual motility was 65%, and the amount of boar semen production for one month in October, namely 60 doses / boar. Conclusions from this study are that in general the percentage of fresh boar semen in the UPT BIBD in Bali covers volume of sperm, motility, and total boar semen production matching the target and semen worth to for distribution.  Keywords : percentage of semen motility, semen dilution, boar semen